Experimental study on fuzzy PID control for DVSCMG based on decoupling feedback linearization - Liping Wu; Yu Guo; Lu Wang; Zhen Yu; Chenxing Zhong (Proceedings of 2014 International Conference on Modelling, Identification & Control, 2014)
In this paper, a decoupling algorithm combined with input-output feedback linearization is derived for a double frame variable speed control moment gyroscope (DVSCMG) to transform the MIMO nonlinear coupling model of DVSCMG into two equivalent SISO subsystems. To improve the accuracy and swiftness, a fuzzy PID strategy based on the linearized subsystems is proposed for the DVSCMG, in which the parameters of PID controllers are adjusted by fuzzy algorithm online. Experimental results on ECP Model 750 verify the effectiveness of the proposed strategy.